133k views
0 votes
How do I solve this equation:
-5(n-1)=7(n+3)

User Ben Vitale
by
5.2k points

2 Answers

2 votes

Answer:

-3/4

Explanation:

The First step is to distribute the 7 in the second part of parentheses.

-5+5-7n=21

-5-7n=21+5

Then collect the terms

-12n=16

Lastly distribute both sides by -12

And the answer is -3/4

User Matt Cashatt
by
4.7k points
1 vote
-5(n-1) = 7(n+3)

First, distribute the 5 in the first parentheses.

-5n+ 5 = 7(n+3)

Next, distribute the 7 in the second set of parentheses.

-5n + 5 = 7n + 21

Subtract 7n from both sides.

-5n + 5 -7n = 21

Subtract 5 from both sides.

-5n - 7n = 21 + 5

Collect like terms.

-12n = 16

Divide both sides by -12

Answer -3/4
User Aaron Stuyvenberg
by
5.3k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.